Factors Affecting Local Coffee Shop Preferences of Students - Villagonzalo, Benjamin Jr; Mazzeo, Helene; Fuentes, Sheryl; Mananquil, Ann Margaret; Monroy, Aila Mae; Namoco, Kyarra Fionna; Pa-alan, Ella Shane (Journal of Interdisciplinary Perspectives, 2025)
This study aims to identify the key factors influencing university students’ choice of local coffee shops in Dumaguete City, addressing the gap in understanding their consumer behavior. Specifically, it examines how demographics and factors such as service, environment, product quality, and pricing affect their preferences. A quantitative approach was used, with surveys distributed to 206 third-year BSBA students from Negros Oriental State University Main Campus I. Results showed that most respondents were 20–21 years old, female, and majoring in financial management, with a daily allowance of ₱51.00–₱100.00. Most visited coffee shops five times or less per month, with Don Macchiato being the most preferred. Among the factors, pricing received the highest average rating (M = 4.65), followed by environment (M = 4.57), service (M = 4.49), and product quality (M = 4.28). These ratings reflect the importance of affordability, ambiance, staff efficiency, and product satisfaction in shaping student choices. The findings offer practical insights for local coffee shop owners and entrepreneurs to develop student-centered strategies that enhance customer appeal and loyalty.